2013
DOI: 10.2196/jmir.2705
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Relationship of Realspace Events and Messages in Cyberspace: Case Study of Influenza and Pertussis Using Tweets

Abstract: BackgroundSurveillance plays a vital role in disease detection, but traditional methods of collecting patient data, reporting to health officials, and compiling reports are costly and time consuming. In recent years, syndromic surveillance tools have expanded and researchers are able to exploit the vast amount of data available in real time on the Internet at minimal cost. Many data sources for infoveillance exist, but this study focuses on status updates (tweets) from the Twitter microblogging website.Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 20 publications
5
72
0
Order By: Relevance
“…It was demonstrated that the trend fitted well with the time line of the major events related to the Marseille Fire. In other works [32][33][34], observable correlations between tweets aggregated by time intervals and disease occurrences were found to be statistically significant. This further suggested the feasibility of using social media text streams as an analogue to different types of events in our society.…”
Section: Related Workmentioning
confidence: 73%
“…It was demonstrated that the trend fitted well with the time line of the major events related to the Marseille Fire. In other works [32][33][34], observable correlations between tweets aggregated by time intervals and disease occurrences were found to be statistically significant. This further suggested the feasibility of using social media text streams as an analogue to different types of events in our society.…”
Section: Related Workmentioning
confidence: 73%
“…The growing popularity of Twitter among teenagers and young adults may provide opportunities for understanding indoor tanning behaviors and resulting injuries. The social networking service has been used to track the spread of infectious diseases such as influenza [11], H1N1 [12], pertussis [13], and foodborne illness [14]. Similar to foodborne illnesses, acute health consequences of tanning bed use, such as burns, are not routinely monitored or reported.…”
Section: Introductionmentioning
confidence: 99%
“…These activity traces are embedded in search queries [36,, social media messages [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92], and web server access logs [34,72,93]. At a basic level, traces are extracted by counting query strings, words or phrases, or web page URLs that are related to the metric of interest, forming a time series of occurrences for each item.…”
Section: Author Summarymentioning
confidence: 99%
“…When appropriately trained, these methods can be quite accurate; for example, many of the cited models can produce near real-time estimates of case counts with correlations upwards of r = 0.95. The collection of disease surveillance work cited above has estimated incidence for a wide variety of infectious and noninfectious conditions: avian influenza [52], cancer [55], chicken pox [67], cholera [81], dengue [50,53,84], dysentery [76], gastroenteritis [56,61,67], gonorrhea [64], hand foot and mouth disease (HFMD) [72], HIV/AIDS [75,76], influenza [34,36,54,57,59,62,63,65,67,68,71,74,[77][78][79][80]82,83,[85][86][87][88][89][90][91][92][93], kidney stones [51], listeriosis [70], malaria [66], methicillin-resistant Staphylococcus aureus (MRSA) [58]<...>…”
Section: Author Summarymentioning
confidence: 99%